Gender gaps in time devoted to Commuting: Evidence from Peru, Ecuador, Chile, and Colombia - Juan Carlos Campa\~na; J. Ignacio Gimenez-Nadal (Global Labor Organization (GLO), 2022)
We analyze the relationship between gender and the time devoted to commuting by men and women in Latin American Countries. Using data from time surveys from Peru (2010), Ecuador (2012), Chile (2015) and Colombia (2012 and 2017), we observe in the four countries, that women devoted less time to this activity compared to men. We find that among the possible justifications for these gender gaps, it is important to consider the presence of children in the household, the hours of work and the type of employment of individuals. These results illustrate the importance of studying this topic in countries where the evidence is scarce mainly due to limitations in comparing the data between countries.
Keywords: D10; J22; 330; Time Use; Commuting; Gender Gaps; Latin America countries